Beyond Boundaries : Exploring into Digital Art! - Aslina, Mohd Jainal; Anuar, Ayob; Zairun, Roslan (UNIMAS Publisher, 2024)
Welcoming the first batch of Foundation Computing students to PRL1053 Digital Art at UNIMAS is a significant milestone. The Digital Art course, offered by the Fine Arts Program since 2000, has traditionally been exclusive to Fine Arts students. This marks the first time it has been made available to students from another program at UNIMAS, broadening its reach and impact. This course equips students with foundational knowledge and skills to create remarkable artwork using digital media software and tools. Impressively, many of these students entered the course with no prior background in art. Yet, their creativity and passion have driven them to excel, producing exceptional work in every project.